2015
DOI: 10.1002/jcc.23990
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption‐induced changes of intramolecular optical transitions:PTCDA/NaCl and PTCDA/KCl

Abstract: Structural and optical properties of isolated perylene-3,4,9,10-tetracarboxylic acid dianhydride molecules adsorbed on (100) oriented NaCl and KCl surfaces were studied theoretically to analyze the recently observed red-shift of the optical excitation spectrum after adsorption (Müller et al., Phys. Rev. B, 2011, 83, 241203; Paulheim et al. Phys. Chem. Chem. Phys., 2013, 15, 4906). The ground-state structures were obtained by periodic dispersion-corrected density functional theory (DFT) calculations. For the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 58 publications
5
37
0
Order By: Relevance
“…Consequently, they attributed E gas-dilute solely to the polarization of the alkali-metal halide substrate assuming a vanishing polarizability of He (identical to vacuum). However, recent DFT calculations came to a different conclusion, namely that PTCDA is bent markedly due to the bonding with the NaCl(100) surface [72][73][74]. The authors of Ref.…”
Section: Comparison With Ptcda On Nacl(100) and Kcl(100)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they attributed E gas-dilute solely to the polarization of the alkali-metal halide substrate assuming a vanishing polarizability of He (identical to vacuum). However, recent DFT calculations came to a different conclusion, namely that PTCDA is bent markedly due to the bonding with the NaCl(100) surface [72][73][74]. The authors of Ref.…”
Section: Comparison With Ptcda On Nacl(100) and Kcl(100)mentioning
confidence: 99%
“…The authors of Ref. [74] computed the absorption energies for the gas-phase molecule and for an isolated molecule on the alkali-metal halide surface which, according to them, differ by 114 meV (for the 6-311G * basis set), of which E dist = 26 meV are caused by molecular distortion and E elec = 36 meV by electrostatic interaction between PTCDA and NaCl. While these numbers depend on the employed basis set, they demonstrate nonetheless that more factors contribute significantly to the measured shift E gas-dilute than merely the substrate polarizability.…”
Section: Comparison With Ptcda On Nacl(100) and Kcl(100)mentioning
confidence: 99%
“…On KCl, PTCDA forms a commensurate brickwall structure [112]. DFT calculations [113] have shown that a single PTCDA molecule on a KCl or NaCl terrace prefers an adsorption site in which the perylene backbone is positioned above a Cl − anion at a distance of 2.72 Å and 2.54 Å, respectively, while the oxygens atoms are located close to the cations in the surface. This leads to a distortion of the molecule similar to the situation on Ag (100) and Ag (110) but with an even more pronounced downward shift of the carboxylic oxygen atoms.…”
Section: Bonding Of Ptcda On Inorganic Surfacesmentioning
confidence: 99%
“…This observation is consistent with the results by Müller et al on PTCDA adsorbed on KCl thin films on Ag(100) [58] who reported that the vibrational modes of the adsorbed molecule are very similar to those of the free molecule, but due to the presence of the substrate additional low energy modes couple to the transition. This was further confirmed by DFT calculations where the redshift of the first optical excitation was found to stem from both the distortion of the molecule due to the interaction with the surface and the electrostatic potential of the surface play an important role [110].…”
Section: B Influence Of Coulomb Interactionsmentioning
confidence: 55%